Clinical heterogeneity of pediatric hepatocellular carcinoma. Issue 6 (19th April 2020) - D'Souza, Amber M.; Towbin, Alexander J.; Gupta, Anita; Alonso, Maria; Nathan, Jaimie D.; Bondoc, Alex; Tiao, Greg; Geller, James I.
Abstract: Background: Hepatocellular carcinoma (HCC) is often a chemoresistant neoplasm with a poor prognosis. Pediatric HCC may reflect unique biological and clinical heterogeneity. Procedure: An IRB‐approved retrospective institutional review of patients with HCC treated between 2004 and 2015 was undertaken. Clinical, radiographic, and histologic data were collected from all patients. Results: Thirty‐two patients with HCC, median age 11.5 years (range 1‐20) were identified. Seventeen patients had a genetic or anatomic predisposition. Histology was conventional HCC (25) and fibrolamellar HCC (7). Evans staging was 1 (12); 2 (1); 3 (10); 4 (9). Sixteen patients underwent resection at diagnosis and five patients after neoadjuvant chemotherapy. Surgical procedures included liver transplantation (LT, 11), hemihepatectomy (9), and segmentectomy (1). Eighteen patients had medical therapy (13 neoadjuvant, 5 adjuvant). Most common initial medical therapy included sorafenib alone (7) and cisplatin/doxorubicin‐based therapy (8). Overall, 14 (43.8%) patients survived with a median follow‐up of 58.8 months (range 26.5‐157.6). Cause of death was most often linked to lack of primary tumor surgery (11). Of the survivors, Evans stage was 1 (11), 2 (1), and 3 (2, both treated with LT). Four of 18 patients (22%) who received medical therapy, 8 of 17 patients with a predisposition (47%), and 14 of 21 patients (66%) who underwent surgery remain alive. Conclusions: Genetic and anatomic predisposing conditions were seen in over half of this cohort. Evans stage 1 or 2 disease was linked to improved survival. LT trended toward improved survival. Use of known chemotherapy agents may benefit a smaller group of pediatric HCC and warrants formal prospective study through cooperative group trials.